An Optimized Dual-Surgeon Simultaneous Orthotopic Hind-Limb Allotransplantation Model in Rats - Sacks, Justin M.; Kuo, Yur-Ren; Horibe, Elaine K.; Hautz, Teresa; Mohan, Kriti; Valerio, Ian L.; Lee, W.P. Andrew (Journal of Reconstructive Microsurgery, 2012)
Composite tissue allograft (CTA) transplantation is a promising treatment in reconstructive surgery for complex tissue injuries in humans. However, continued research is required to optimize the risk to benefit ratios. In this study, we describe, in detail, an optimized simultaneous dual-surgeon orthotopic hind-limb transplantation model in direct comparison to a single-surgeon model. In this study 75 hind-limb CTAs were performed, employing either a dual-surgeon model (n = 60) or a single-surgeon model (n = 15) for the transplantation of two hind-limbs. Operative times, complication rates, and costs were compared. The dual-surgeon approach showed a significant reduction of 45.4% in overall operative time (p < 0.05). Overall complication rate was 8%. The dual-surgeon model was ∼30.5% more cost-effective than the traditional single-surgeon approach. Benefits of the proposed simultaneous dual-surgeon orthotopic rat hind-limb CTA model include decreased operating times, decreased complication rates, and reduced financial costs when compared with the established single-surgeon model.
Keywords: hind-limb; allotransplantation; rat; experimental model; orthotopic